Forensic characteristics and phylogenetic analyses of one branch of Tai‐Kadai language‐speaking Hainan Hlai (Ha Hlai) via 23 autosomal STRs included in the Huaxia™ Platinum System. Issue 10 (30th August 2020) - Li, Wenhui; Wang, Xianwen; Wang, Xiehong; Wang, Fenfen; Du, Zhengming; Fu, Fangshu; Wu, Wenlong; Wang, Shuya; Mu, Ziqing; Chen, Chunwei; Hu, Xiaomin; Ding, Jiuyang; et al.
Abstract: Background: Hainan Island, located in the South China Sea and separated from the Leizhou Peninsula by Qiongzhou Strait, is the second largest island after Taiwan in China. With the expansion of Han Chinese and the gradual formation of "South Hlai and North Han", nowadays, Hainan Hlai is the second largest population after Han Chinese in Hainan Island. Ha Hlai, distributed in southwest and southern Hainan Island, is the dominant branch of Hlai and speaks Ha localism. Methods: We utilized the Huaxia ™ Platinum PCR Amplification System (including 23 autosomal STRs and 2 sex‐linked markers) to obtain the first STR profiling batch of 657 Ha Hlai individuals (497 males and 160 females). In order to explore the genetic relationships between the studied Ha Hlai and other reference populations with different language families, population genetic analyses, including PCA, MDS, STRUCTURE, and phylogenetic analysis, were conducted based upon the raw data and allelic frequencies of the polymorphic autosomal STR markers. Results: In total, 271 distinct alleles were observed at the 23 STR loci. The number of diverse alleles ranged from 7 at TPOX locus to 23 at FGA locus, and the allelic frequencies varied from 0.0008 to 0.5533. In addition, the CPE and CPD were 1‐7.39 × 10 −10 and 1‐3.13 × 10 −28, respectively. The phylogenetic analyses indicated that Ha Hlai is a Tai‐Kadai language‐speaking and relatively isolated population which has a close genetic and geographical relationship with Hainan Hlai, and M95 is the dominant haplogroup in Ha Hlai (56.18%). Conclusion: The 23 autosomal STR genetic markers were highly polymorphic as well as potentially useful for forensic applications in Hainan Ha Hlai population. The phylogenetic analyses demonstrated that small geographic scale gene flows could not be ignored and the shaping of the unique gene pool for each population was the combination effects of geographic, language, and cultural isolations. Abstract : The first batch of 23 autosomal STR profiles of Ha Hlai, one important branch of Hainan Li (Hlai), were obtained and reported by genotyping 657 Ha Hlai individuals (497 males and 160 females) utilizing the Huaxia™ Platinum PCR Amplification System. The analyses and comparisons of all these allelic frequencies and forensic statistical parameters demonstrated that the 23 autosomal STR genetic markers included in Huaxia™ Platinum PCR Amplification System were highly polymorphic as well as potentially useful for forensic applications in Hainan Ha Hlai population. Ha Hlai is a Tai‐Kadai language‐speaking and relatively isolated population which has a relatively close relationship with Hainan Hlai, and the haplogroup M95 is the dominant haplogroup in Ha Hlai (56.18%), which demonstrated that the relatively small geographic scale gene flows, especially for the multi‐ethnic mixed areas, could not be ignored and the shaping of the unique gene pool for each population the co‐effects of geographic, language, and cultural isolations.